ANALISIS PENGARUH JUMLAH PENDUDUK, PENDIDIKAN, TINGKAT PARTISIPASI ANGKATAN KERJA, UPAH MINIMUM KABUPATEN/KOTA DAN PRODUK DOMESTIK REGIONAL BRUTO TERHADAP PENGANGGURAN TERBUKA DI PROVINSI JAWA BARAT TAHUN 2018-2021 - Putra, Ghora Vira Handy; Hidayah, Nur (KOMITMEN: Jurnal Ilmiah Manajemen, 2023)
This study aims to find out how the effect of Population, Education, Labor Force Participation Rate, Regency/City Minimum Wage and Gross Regional Domestic Product has on open unemployment in West Java province in 2018-2021. This research data uses secondary data types in the form of combined panel data between cross-section data and time series data for 4 years starting from the 2018-2021 period. The data sources used were obtained from the Central Bureau of Statistics (BPS) and the Office of Manpower. Secondary data is data that is not taken directly, namely data taken from previous research or published libraries. The results of this study show that Population and Education have no effect on Open Unemployment in West Java Province in 2018-2021. The Labor Force Participation Rate variable has a negative effect on Open Unemployment in West Java Province in 2018-2021. District/City Minimum Wage Variable has a positive effect on Open Unemployment in West Java Province in 2018-2021. The Gross Regional Domestic Product variable has an effect negative towards Open Unemployment in West Java Province in 2018-2021. Implementation of policies taken by the government to overcome the response by creating wider employment opportunities, the government assists with knowledge insight and entrepreneurial spirit skills to MSMEs in the form of technical and management guidance, building social institutions that can guarantee an unemployed life.Â